Comparative Accounting – Is It Still Relevant in Today’s Global Era of Convergence? - Wan Abdul Rahim, Wan Fuziraihan; Mastuki, Shahrul Zariah; Nawi, Yusni; Alfan, Ervina (Asian Journal of Accounting Perspectives, 2009)
This essay discusses the relevance of comparative accounting in the midst of convergence efforts championed by the international accounting standard setter – the International Accounting Standards Board (IASB). Obstacles to comparability in reference to respective countries’ various attributes, namely the regulatory regime and capital market are discussed. In addition, other specific factors such as business and financial environments as well as accounting and auditing culture are also discussed. The essay concludes that although the process of convergence is swiftly taking place worldwide, comparative accounting still remains an important topic to address within all international accounting subjects.